Монгол дахь улс төрийн боловсролын хөгжил: уламжлал шинэчлэл - Д.Отгончимэг (Politology, 2024)
In my presentation I’d like to stress on historic role of political science for Mongolia. For that reason, I studied periodically about the system, through which political education taught to well-trained staff, and secular political education taught under Mongolian Republic Revolutionary Party in the name of Marx method and theory through the framework such as political agitation, advertisements, and books, parties, unions and Mongolian Revolutionary Youth. Товч утга: Монгол улсад улс төрийн боловсрол мэдлэг олгож ирсэн түүхэн үйл явцыг тоймчлон авч, тэдгээрийн гол ач холбогдлыг төр, нийгмийн зүгээс ард иргэдэд хэрхэн ямар шат дамжлагатайгаар явуулж байсан түүхэн уламжлалын онцлогуудыг гаргахыг зорьсон.